Immunologic response to recombinant hirudin in HIT type II patients during long-term treatment - Huhle, Günter; Hoffmann, Ursula; Song, Xuehong; Wang, Lianchun; Heene, Dieter L.; Harenberg, Job (British journal of haematology, 1999)
We prospectively investigated 27 patients with heparin-induced thrombocytopenia (HIT) type II who were subsequently treated with r-hirudin. Patients with venous or arterial thromboembolism were treated with activated partial thromboplastin time (aPTT)-controlled intravenous r-hirudin (n = 19; mean 19.3 d) followed by subcutaneous r-hirudin (n = 6; mean 22.5 d) and oral anticoagulation. Patients without thromboembolism were treated with subcutaneous r-hirudin (n = 8; mean 25.9 d). Four patients were readmitted to subcutaneous r-hirudin for a mean duration of 32 d. The incidence of r-hirudin antibodies was 84% for intravenously treated patients and 50% in subcutaneously treated patients. The patients (n = 27) showed a 74% overall incidence of r-hirudin antibodies, mainly of the IgG-subclass, without seroconversion before day 6 and after day 32 of r-hirudin treatment or during r-hirudin treatment. None of the patients showed onset or recurrence of venous or arterial thromboembolism, systemic allergic reactions or IgE-antibody development. During intravenous and subcutaneous administration of r-hirudin the aPTT and the ecarin clotting time was increased in the antibody-positive patients compared to antibody-negative patients. Therefore we assume that r-hirudin antibodies may reduce r-hirudin metabolism.
Elektronische Reproduktion der Druck-Ausgabe 25 Dezember 2001
Gesehen am 05.05.2022